Livestock trade and devolution in the Somali-Kenya transboundary corridor - Philemon Ong’ao Ng’asike; Finn Stepputat; Jesse Theuri Njoka (Pastoralism, 2020)
Abstract After the collapse of the central Somali state in 1991, Somali livestock trade has increasingly been re-oriented towards terminal markets in central and coastal Kenya, helped by the more recent trade liberalization in Kenya. The predominantly informal cross-border trade (ICBT) has nurtured local livelihoods and government revenues in Kenya, where informal transactions and formal regulation overlap in the Somali-fed livestock supply chains. This article analyses the practices and dynamics that characterize Somali-Kenyan cross-border livestock trade, and proceeds to point out important policy issues that have emerged after the devolution of key state functions and regulation to county governments. The article finally highlights areas of collaboration between the national and county governments that are necessary to achieve a credible supply of meat in Kenyan and international markets. By doing so, it explores the linkage between changes in the political economy of cross-border livestock trade, and the unintended impact of decentralization on the governance of livestock supply chains.